Towards a framework for strategic knowledge management practice: Integrating soft and hard systems for competitive advantage. Issue 4 (14th November 2016) - Huang, Fang; Gardner, Scott; Moayer, Sanaz
Abstract : Purpose: This paper aims to address the limitations of current knowledge management (KM) models by presenting a strategic knowledge management (SKM) framework based on a unique configuration of literature concerned with optimising learning and knowledge creation at the interface between human (soft) and information and communication technology (hard) networks. Design/methodology/approach: This paper revisits the key tenets and most frequently cited models in the existing literature, summarises their common elements, clarifies the interrelationships between the hard and soft KM processes and practices and systemically incorporates these previously separate and independent elements into a new integrated conceptual framework. Then, it identifies key organisational factors which could facilitate this integration and leverage the value generated from different systems embedded in this model. Findings: The paper highlights the key elements and applications of a new SKM conceptual model for actively and purposefully integrating explicit and tacit knowledge embedded within organisation systems and broader social and business intelligence networks. Practical implications: The application of the thinking, organising principles and management practices derived from the SKM framework with its unique characteristics that are hard to substitute or imitate may support improvement and/or innovation of processes, products, services and brands contributing to sustainable competitive advantage of the firm. Originality/value: While both hard and soft KM systems have been individually identified by previous studies as integral to KM, the research is amongst the first attempts to explore how to integrate both systems within a strategic KM framework with supporting organisational design principles for creating firm competitive advantage.